Caspase-1 deficient mice are more susceptible to influenza A virus infection with PA variation - Huang, Chih-Heng; Chen, Chi-Jene; Yen, Chia-Tsui; Yu, Cheng-Ping; Huang, Peng-Nien; Kuo, Rei-Lin; Lin, Sue-Jane; Chang, Cheng-Kai; Shih, Shin-Ru (The Journal of infectious diseases, 2013)
Reassortment within polymerase genes causes changes in the pathogenicity of influenza A viruses. We previously reported that the 2009 pH1N1 PA enhanced the pathogenicity of seasonal H1N1. We examined the effects of the PA gene from the HPAI H5N1 following its introduction into currently circulating seasonal influenza viruses. To evaluate the role of H5N1 PA in altering the virulence of seasonal influenza viruses, we generated a recombinant seasonal H3N2 (3446) that expressed the H5N1 PA protein (VPA) and evaluated the RNP activity, growth kinetics, and pathogenicity of the reassortant virus in mice. Compared with the wild-type 3446 virus, the substitution of the H5N1 PA gene into the 3446 virus (VPA/3446) resulted in increased RNP activity and an increased replication rate in A549 cells. The recombinant VPA/3446 virus also caused more severe pneumonia in Casp 1(-/-) mice than in IL1β(-/-) and wild-type B6 mice. Although the PA from H5N1 is incidentally compatible with a seasonal H3N2 backbone, the H5N1 PA affected the virulence of seasonal H3N2, particularly in inflammasome-related innate immunity deficient mice. These findings highlight the importance of monitoring PA reassortment in seasonal flu, and confirm the role of the Caspase-1 gene in influenza pathogenesis.